Carbohydrates in Grain Legume Seeds: Improving Nutritional Quality and Agronomic Characteristics - Hedley, C.L (CABI, 2014)
Grain legumes have been an important part of the social evolution of mankind over the past 10,000 years, carbonized remains having been discovered in Neolithic settlements. In more recent times, however, these crops have become less fashionable, particularly in Europe and North America, as the consumption of meat has increased and economic pressures have promoted the growth of cereal monocultures in agricultural systems. The increasing awareness of environmental problems caused by pollution from the over use of fertilizers and a growing interest in more healthy diets is again focusing interest on to this important group of plants. The neglect of grain legumes has resulted in crops that are relatively underdeveloped compared with cereals such as maize, wheat and rice. These crops have been subjected to intensive scientific and technological investigations following substantial public and private financial investment. It is hoped that this book will begin the process of rectifying this imbalance.